Europec 2015 2015
DOI: 10.2118/174364-ms
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Well Productivity Through Controlling Fines Migration and Scale Formation

Abstract: The intrusion of formation fines and formation sand grains into the proppant pack drastically reduces the conductivity of propped fractures, which can negatively impact well production. This paper describes the development and field treatments using a new form of surface modification agent (SMA) that is a low-tackiness surface modification agent (LTSMA) that can be applied during primary hydraulic fracturing or remedial treatments of propped fractures. Studies were conducted to demonstrate the mechanisms by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Due to hydrophobe interactions through VDW bonds, a strong molecular hook-and-latch system is formed between fines and the fracture surface, thus providing an increased adhesive force . Several experimental and field studies have demonstrated that chemical methods successfully prevent fines migration, even under high flow rates and flow interruptions, with no observed reduction in permeability. …”
Section: Implications For Field-scale Fines Controlmentioning
confidence: 99%
“…Due to hydrophobe interactions through VDW bonds, a strong molecular hook-and-latch system is formed between fines and the fracture surface, thus providing an increased adhesive force . Several experimental and field studies have demonstrated that chemical methods successfully prevent fines migration, even under high flow rates and flow interruptions, with no observed reduction in permeability. …”
Section: Implications For Field-scale Fines Controlmentioning
confidence: 99%
“…Dendrimers have been paid extensive attention since the first synthesis because of their unique characteristics such as highly ordered structure, narrow size distribution, and uniform dense terminal functional groups, which render the polymers as ideal candidates in a wide range of applications (Abdel Rehim et al, 2010;Mo et al, 2008). Recent studies have shown that dendrimers have potential application in the area of oilfield chemistry (Amanullah, 2013;Kaiser, 2013;Lai et al, 2013;Li et al, 2012;Rivers et al, 2011;Stanciu et al, 2015). As far as drilling fluid is concerned, Amanullah (2013) illustrated a promising potential of developing high performance drilling fluid in future challenging conditions with the use of dendrimers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, resin coated proppant technology was the common method to solve proppant flowback [12,13]. During the past decades of development, two main methods were formed and were widely used on site: pre-cured proppants and curable proppants [14 -16].…”
Section: Introductionmentioning
confidence: 99%